Adaptive energy shaping control of a class of nonlinear soft continuum manipulators - Franco,E; Garriga,Casanovas A; Tang,J; Rodriguez,y Baena F; Astolfi,A (IEEE-ASME Transactions on Mechatronics, 2022)
Soft continuum manipulators are characterized by low stiffness which allows safe operation in unstructured environments but introduces under-actuation. In addition, soft materials such as silicone rubber, which are commonly used for soft manipulators, are characterized by nonlinear stiffness, while pneumatic actuation can result in nonlinear damping. Consequently, achieving accurate control of these systems in the presence of disturbances is a challenging task. This paper investigates the model-based adaptive control for soft continuum manipulators that have nonlinear uniform stiffness and nonlinear damping, that bend under the effect of internal pressure, and that are subject to time-varying disturbances. A rigid-link model with virtual elastic joints is employed for control purposes within the port-Hamiltonian framework. The effects of disturbances and of model uncertainties are estimated adaptively. A nonlinear controller that regulates the tip orientation of the manipulator and that compensates the effects of disturbances and of model uncertainties is then constructed by using an energy shaping passivity-based approach. Stability conditions are discussed highlighting the beneficial role of nonlinear damping. The effectiveness of the controller is assessed with simulations and with experiments on a soft continuum manipulator prototype.